The Effect of Parent-Child Relationship to Middle Childhood’s Empathy Skill - Afra Nada Syafira (Psibernetika, 2022)
Empathy that appears in children can be caused by how the relationship that children build with their parents. This study aims to prove the influence of the relationship of parents and children on the middle childhood children’s ability to empathize. The method used in this study is a quantitative method with simple linear regression analysis technique. The samples in this study amounted to 184 parents with children aged 6-11 years who live together and directly take care of their children without much help from others in the city of Pekanbaru. The sample was collected through purposive sampling technique. The instruments used in this research are the adaptation of the Basic Empathy Scale - Parent Report (BES-PR) and Child Parent Relationship Scale (CPRS). The results of the study showed that there is an effect of the relationship between parents and children on middle childhood children’s ability to empathize by 16.1%. The middle childhood children's ability to empathize in this study was in the high (95.7%) and low (4.3%) level, while the relationship between parents and middle childhood childrens in all samples of this study was in the good category (100%).